BIOMARKER COMPOSITION OF HIGHER PLANT MACROFOSSILS FROM LATE PALAEOZOIC SEDIMENTS - Auras S.; Püttmann W.; Wilde V.; Hoernes S.; Scheffler K. (My University, 2006)
The main objective of the present study was to clarify if the fernane derivatives 5-methyl-10(4-methylpentyl)-des-A-25-norferna-5,7,9-triene (MATH), 25-norferna-5,7,9-triene (MAPH), 24,25-dinorferna-1,3,5,7,9-pentaene (DAPH 1) and iso-25-norferna-1,3,5,7,9-pentaene (DAPH 2) can securely be assigned to one of the three previously proposed source plant groups from some Euramerican Upper Carboniferous coals (uppermost Westphalian and Stephanian). For this purpose remains of conifers, cordaites and pteridosperms were isolated from core and outcrop material from different Euramerican coal basins (e.g. Saar-Nahe Basin, Blanzy-Montceau Basin). Results show that MATH, MAPH, DAPH 1 and DAPH 2 were present in all extracts of cordaite remains. In the sediments surrounding the cordaite macrofossils, the compounds were either not detectable or have been found only in comparatively small amounts obviously due to impregnation originating from imbedded cordaites. Contrarily, the compounds were not detected in the extractable organic matter of conifer macrofossils derived from the Saar-Nahe Basin, from Bletterbach (South Tyrole, Italy), and from Frankenberg (Hessen, Germany). The same is true for remains of horsetails (Calamites), giant club mosses (Lepidodendron and Sigillaria), and ferns (Pecopteris) from the Saar-Nahe Basin which have been studied for comparison. The compounds were also lacking in the extractable organic matter of pteridosperms like Alethopteris, Dicroidium, Lescuropteris, Macroneuropteris and Neuropteris, but were detected in minor amounts in some Odontopteris remains from the Blanzy-Montceau Basin (France). However, the sediments surrounding the Odontopteris macrofossils yielded even higher concentrations of the compounds. For this reason, the Odontopteris macrofossils were most likely impregnated by migrating fernane derivatives from the sediment which were possibly originally originating from cordaite remains. Therefore, cordaites can most probably be considered as one and, possibly, the only biological source of the precursor molecules of the fernane derivatives MATH, MAPH, DAPH 1 and DAPH 2 in the Upper Carboniferous coal basins. © 2006 Elsevier B.V. All rights reserved.
Keywords: BIOMARKER ANALYSIS; CARBON ISOTOPIC RATIO; CONIFERS; CORDAITES; FERNANE DERIVATIVES; PTERIDOSPERMS; Carboniferous; Paleozoic::Carboniferous; Палеозой::Каменноугольная